Adminisprudence : a behavioural approach to managing ourselves and others - Udom, Udoh Elijah (Ibadan : Spectrum ; Oxford : African Books Collective, 1999)
Provides insights into effective management of human resources in corporate bodies, positing that the practice of human management is an ineducible requirement necessary for success in business.
Includes bibliographical references and index.
oif 05/02/15
Loan
Keywords: Personnel management -- Handbooks, manuals, etc; Industrial relations -- Handbooks, manuals, etc; Management -- Handbooks, manuals, etc